Production and Purification of Shark and Camel Single‐Domain Antibodies from Bacterial and Mammalian Cell Expression Systems. Issue 6 (17th June 2022) - Duan, Zhijian; Buffington, Jesse; Hong, Jessica; Ho, Mitchell
Abstract: Single‐domain antibodies, including the antigen‐binding variable domains of the shark immunoglobulin new antigen receptor and the camelid variable region of the heavy chain, are the smallest antigen recognition domains (∼15 kDa) and have unique characteristics compared to conventional antibodies. They are capable of binding epitopes that are hard to access for classical antibodies and can also be used for therapeutics or diagnostics or as modular building blocks for multi‐domain constructs, antibody‐drug conjugates, immunotoxins, or chimeric antigen receptor therapy. This article contains detailed procedures for the purification and validation of two single‐domain antibodies (one shark and one camel), which bind to the S2 subunit of the SARS‐CoV‐2 spike protein, using both bacterial and mammalian cell expression systems. It provides a comprehensive reference for the production of single‐domain antibodies with high yield, good quality, and purity. © Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol : Production of single‐domain antibodies from Escherichia coli Alternate Protocol : Production of single‐domain antibodies using the mammalian cell line Expi293F Support Protocol 1 : Production and purification of single‐domain antibodies on a small scale with the polymyxin B method Support Protocol 2 : Validation of single‐domain antibodies by ELISA